The uphill journey of smoking cessation in chronic obstructive pulmonary disease: why a well-built vehicle matters - Jakobsen, Rasmus Kragh; Farver-Vestergaard, Ingeborg; Løkke, Anders (Frontiers in Health Services, 2025)
IntroductionSmoking cessation remains among the most effective interventions for improving outcomes in patients with chronic obstructive pulmonary disease (COPD). Quitting smoking slows disease progression, reduces morbidity, improves quality of life and increases life expectancy. However, a substantial proportion of patients with COPD continue to smoke, and generic cessation strategies often fall short in this population. While most cessation research targets “healthy” smokers, individuals with COPD face additional challenges – including higher nicotine dependence and psychological comorbidities – that complicate quit attempts.MethodsThis mini-review summarises randomised controlled trials (RCTs) investigating smoking cessation interventions in COPD.ResultsOur study reveals wide variability in the intensity, duration and components of interventions, with only a minority achieving long-term abstinence. Notably, two high-performing studies stand out for their comprehensive, long-term and individualised approaches. These findings suggest that success in smoking cessation for patients with COPD relies not only on the right intervention components but also on the construction, durability and sustained support.ConclusionTo support and sustain smoking cessation among patients with COPD, multicomponent, high-intensity and long-duration interventions tailored to individual needs appear to be required, with an emphasis on ongoing support and frequent follow-up.